Avaliação da resistência de união de sistemas adesivos universais a dentina hígida e afetada por cárie - Alves, Alice de Rosso (2024)
The aim of this study was to evaluate the immediate dentin bond strength of a universal adhesive system, Scotchbond Universal Plus (3M ESPE), in comparison to its predecessor, Single Bond Universal (3M ESPE), using different application strategies (etch-and-rinse and self-etch) and under different substrate conditions (sound and affected dentin). A total of 40 freshly extracted, sound mandibular bovine incisors were randomly divided into 8 groups (n=5) according to the substrate condition (sound and affected by a 14-day cariogenic pH-cycling challenge) and application strategy (etch-and-rinse and self-etch). The adhesive systems were applied on the dentin surface following the manufacturer’s instructions, and composite resin cylinders were formed using starch tubes (internal diameter of 0.96 mm and height of 1 mm). Six composite resin cylinders (specimens) were obtained from each tooth. The specimens were stored in distilled water at 37°C for 24 hours. Each tooth's specimens underwent micro-shear bond strength testing at a crosshead speed of 1 mm/min, and after fracture, the failure mode was observed under a stereomicroscope. Bond strength data in MPa were subjected to statistical analysis to compare the variables and their interactions. No significant interactions were observed between substrate condition, adhesive system, and application strategy. Three-way ANOVA revealed significant effects of substrate (p=0.035) and adhesive system (p<0.001). Scotchbond Universal Plus (3M ESPE) exhibited lower bond strength values compared to its predecessor, and bond strength values to affected dentin were lower than those to sound dentin. Interfacial failure patterns were common across all groups. In conclusion, the new adhesive Scotchbond Universal Plus (3M ESPE) performed worse than its predecessor in the micro-shear bond strength test, without promoting better adhesion to affected dentin, regardless of the adhesive strategy used. Furthermore, the substrate condition influenced bond strength, with affected dentin showing lower values.